Prevention of sexual harassment: the Islamic approach - Ali Mohamed, Ashgar Ali (penseejournal.com, 2014)
Sexual harassment is a common phenomenon today in the workplaces and tertiary educational institutions, among others. The effect is that it destroys family ties and relations. To prevent this nagging problem, Islamic law has made provisions on matters that relate to sexual harassment. It has put in place certain mechanisms to prevent sexual harassment. One way of dealing with this problem is that the legalisation of the institution of marriage and prevention of celibacy. Apart from this, severe punishments await those who commit fornication which is the objective of sexual harassment. Similarly, the Creator has ordain the believers, male and female alike, to lower their gaze and control their sexual organs in such a way that would neither lead them to sexual sins nor should they stare at the opposite sex in such a way as to cause sexual harassment. This shows that it is not allowed for Muslims to put unacceptable lusts in the hearts of others by any form of harassment. In a similar vein, the Messenger of Allah (PBUH) forbade all avenues that can lead to sexual harassment and this includes prohibiting people of different sexes from sitting or from having discussion in a private or secluded area. In addition, Islam does not permit a woman to travel without a ma’hram like her husband, father, uncle, brother or son. On the same token, respect for one’s privacy is highly protected in Islam even with respect to children. Children would need to obtain the permission of their parents before they enter the rooms of their parents in certain periods. This is also a measure to prevent any forms of sexual harassment. Having said the above, this paper will discuss the preventive aspects of sexual harassment from the Islamic law perspective with special focus on the primary sources of Islamic law.